Sécurité nationale et sécurité globale: l'adaptation des services de renseignements francais - Ocqueteau, Frédéric (Canadian journal of criminology and criminal justice, 2006)
Since the terrorist attacks of 11 September 2001, all intelligence services have been encouraged to reorganize, based on the conclusion that their ability to respond to new types of threats was limited. In France, the impetus for change has been twofold. The intelligence services of the ministries of defence and the interior are being asked to cooperate more effectively while remaining secret services. At the same time, a new rhetoric of 'global security,' originating in prefecture offices, seems to have taken root in support of the push for change. The author examines the premises underlying these phenomena, drawing on classified documents. While actual practices are not questioned, the author outlines the nature of the changes sought in the state bureaucracy, which must be carefully kept beyond citizens' control. (English) [ABSTRACT FROM AUTHOR]